OCCURRENCE OF LIASSIC FAUNAS AT WAANEY (UANEI) PROVINCE OF BAY, SOUTH—WESTERN SOMALIA (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2020)
The sequence exposed at Waaney (South—western Somalia) consists, from bottom to top, of the following horizons: A) Blackish marly limestones, thickness 20 m; B) Grey and greenish marls and shales, thickness 10 m; C) Vacuolar yellowish—grey limestone, thickness 6 m; D) and F) Bioclastic, dark grey limestones in beds up to 1 m thick, thickness 54 m; E) and G) Yellowish—brown or Pink limestones with nodular or brecciated structure, with two levels rich in Ammonites, thickness over 45 m. Sedimentological features give evidences that the environment evolved from restricted lagoon with fine terrigenous supply and probable evaporitic episodes to shallow sea with varying energy conditions and eventually to deeper but partially restricted sea with oligotypic fauna. Fossils collected in the E) and G) levels include about 40 specimens of Ammonites of size varying from 6 to- 15 cm, fossilized in a yellow—grey limestone. The Ammonites of the E) level may be referred to the genus Protogrammoceras (?) and to the species Protogrammoceras madagascariense; the Ammonites of the G) level to the Protogrammoceras madagascariense and to the genus Hildaites. The Ammonite association of. the E) level seems to indicate a Lowermost Toarcian age; the association of the G) level an Early Toarcian age, on the ground of biostntigraphic investigations in the Ethiopian—Indo—Malagasy region and in areas outside this Province.
Keywords: Somalia; Stratigraphy; Liassic; Ammonites; Protogrammoceratinae.